Formulation of Hydroponic Green Vegetable Marketing Strategies in Indonesia as An Effort to Enhance Competitiveness - Lati Sari Dewi (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
This comprehensive analysis focuses on crafting effective marketing strategies for hydroponic vegetables and fostering future development within the industry. Employing a SWOT analysis and adopting a holistic marketing approach, the goal is to create strategies that not only capitalize on strengths but also address weaknesses, seize opportunities, and mitigate threats. These strategies aim to empower industry producers by aligning with integrated economic benefits, ensuring their sustained success. The outcomes of this strategic analysis will serve as invaluable references for promoting hydroponic vegetables. The industry can showcase its sustainability and quality by leveraging strengths such as efficient resource utilization and controlled environments. Addressing weaknesses like public perception challenges and potential high start-up costs will be crucial in developing a well-rounded approach. Seizing opportunities in the growing demand for fresh, locally sourced produce and the increasing interest in sustainable agriculture, the strategies will position hydroponic vegetables as a forward-looking choice. Simultaneously, mitigating threats like market competition and regulatory hurdles will be integral to long-term viability. In essence, the resulting strategies aim to create a resilient marketing framework that promotes hydroponic vegetables and contributes to the overall economic prosperity of industry producers.